Β-catenin Mutations Are Not Involved in Early-stage Hepatocarcinogenesis Induced by Protoporphyrinogen Oxidase Inhibitors in Mice. (June 2017) - Kuwata, Kazunori; Inoue, Kaoru; Ichimura, Ryohei; Takahashi, Miwa; Kodama, Yukio; Shibutani, Makoto; Yoshida, Midori
We previously reported the contribution of constitutive androstane receptor (CAR) in cytotoxicity-related hepatocarcinogenesis induced by oxadiazon (OX) or acifluorfen (ACI), two pesticides categorized as protoporphyrinogen oxidase (PROTOX) inhibitors. The molecular characteristics of preneoplastic and neoplastic lesions induced by OX and ACI were immunohistochemically compared to those by phenobarbital (PB), a typical CAR activator, in wild-type (WT) and CAR knockout (CARKO) mice after diethylnitrosamine initiation. We focused on changes in β-catenin and its transcriptional product glutamine synthetase (GS). In PB-promoted foci and adenomas, nuclear accumulation of mutated β-catenin was increased with high frequency. PB treatment also increased the multiplicity and area of GS-positive foci and adenomas in WT mice. No foci and adenomas showed nuclear accumulation of β-catenin and expression of GS in CARKO mice, similar to both genotypes of mice treated with OX and ACI. Interestingly, hepatocellular carcinoma induced in ACI-treated WT mice showed nuclear accumulation of β-catenin and was positive for GS. Our results indicated that β-catenin mutations were not involved in early-stage hepatocarcinogenesis induced by PROTOX inhibitors in mice, although activation of β-catenin and CAR is important in PB-induced tumorigenesis. The significant differences in molecular profiles suggested involvements of multiple mode of actions for hepatocarcinogenesis induced by PROTOX inhibitors.